José Carlos Mariátegui's Unfinished Revolution: Politics, Poetics, and Change in 1920s Peru - Moore, Melisa (Lexington Books, 2013)
The years 1909–1930, the eleven-year presidency of the businessman-turned-politician Augusto B. Leguía, mark a formative period of Peruvian modernity, witnessing the continuity of a process of reconstruction and the founding of an intellectual and cultural tradition after a humbling defeat during the War of the Pacific (1879–1883). But these years were also fraught with conflict generated by long-standing divisions and new rivalries. A postwar generation of intellectuals and artists, led by José Carlos Mariátegui and galvanized by left-wing thinking and an avant-garde aesthetic, sought representation in the fields of politics and the arts, and participation in the process of reconstruction initiated by a Positivist oligarchy. New political and artistic conceptions raised their awareness of the fractured sense of nationhood in Peru and the need for a new project of nation-formation centered on a common political and cultural consciousness. They also gave rise to divergent political and artistic practices and projects. Amongst these, Mariátegui’s Indigenist-Marxist politics and Modernist-inspired poetics were pivotal in revitalizing, conciliating and channeling those of his cohorts and challengers. Comprising six full-length chapters, a comprehensive Introduction and Conclusion, this monograph is extensive in scale and scope. It provides fresh readings of key writings of Mariátegui, one of Latin America’s most important and revolutionary political, cultural and aesthetic theorists, through the lens of his poetics, emphasizing the value of this approach for a fuller understanding of his work’s political meaning and impact. It does so through detailed analysis of the poetic, expressive language employed in seminal political essays, aimed at forging a new Marxist position in 1920s Peru. Furthermore, it offers powerful and original critiques of understudied intellectuals of this time, especially aprista-Futurist, Socialist and Indigenist female writers and artists, such as Magda Portal and Ángela Ramos, whose work he championed. These readings are fully contextualized in terms of detailed critical study of complex sociopolitical conditions and positions, and bio-bibliographical, intellectual backgrounds of Mariátegui and his contemporaries. The monograph examines and underscores the fundamental importance of Mariátegui’s, and their, politico-poetic practices and projects for forging a national-cum-cosmopolitan, shared, yet also heterogeneous, political culture and cultural tradition in 1920s Peru.